2014
DOI: 10.1128/aac.01382-13
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Functional Role of P-Glycoprotein in Limiting the Oral Bioavailability of Lumefantrine

Abstract: In the quest to explore the reason for the low and variable bioavailability of lumefantrine, we investigated the possible role of P-glycoprotein (P-gp) in lumefantrine intestinal absorption. An in situ single-pass intestinal perfusion study in rats with the P-gp inhibitor verapamil or quinidine and an ATPase assay with human P-gp membranes indicated that lumefantrine is a substrate of P-gp which limits its intestinal absorption. To confirm these findings, an in vivo pharmacokinetic study was performed in rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…42,43 Interestingly, in patients receiving NVP-based ART, the defective variant ABCB1 3435 TT genotype was significantly associated with high lumefantrine plasma concentration. Similarly, a previous study reported nonsignificant increase of lumefantrine clearance (13%) in carriers of homozygous wild type for CYP3A5*3.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Interestingly, in patients receiving NVP-based ART, the defective variant ABCB1 3435 TT genotype was significantly associated with high lumefantrine plasma concentration. Similarly, a previous study reported nonsignificant increase of lumefantrine clearance (13%) in carriers of homozygous wild type for CYP3A5*3.…”
Section: Discussionmentioning
confidence: 99%
“…The number of participants was sufficient to assess our PK objective, but insufficient for determining which patient variables could significantly explain the variability. Interpatient variability in LUM PK exposure may be partially attributed to differences in metabolism due to maturation (age) ; polymorphism of CYP3A4 enzymes ; metabolism or p‐glycoprotein efflux activity in intestinal epithelial cells ; physiological differences that may include food effect on gastric emptying and gastrointestinal (GIT) transit time. Other important factors such as pH of GIT contents may affect drug stability and solubility and hepatic blood flow .…”
Section: Discussionmentioning
confidence: 99%
“…Patient related factors include gastrointestinal {GIT} physiological processes and food effect on absorption [132,135,137,138]. These include alterations in P H of GIT contents and hepatic blood flow [132]; drug efflux by ATP-binding cassette (ABC) transporters pglycoprotein and metabolism at the intestinal mucosa [139,140]. Gastric emptying varies with dietary content, mechanical effects such as volume and state of food, either solid or liquid and food viscosity [133,135,136].…”
Section: Factors Affecting Bioavailability Of Orally Administered Drugsmentioning
confidence: 99%
“…Mechanisms responsible for poor LUM oral bioavailability are attributed to its physicochemical properties and GIT barriers to absorption [139]. The solubility of LUM and availability for absorption is enhanced by dietary fat [91,129,130].…”
Section: Factors Affecting Bioavailability Of Orally Administered Drugsmentioning
confidence: 99%